A Love Letter to Theatre. Robert Cohen. „A Director’s Theatre. The Romanian Theatre from an American Perspective.” Translated by Carmen Borbély and Anca Măniuțiu. Cluj-Napoca: Casa Cărții de Știință Publishing House, 2017. - WOHL, Eugen (Studia Universitatis Babeș-Bolyai Dramatica, 2018)
Familiar to Romanian readers primarily as a renowned Acting professor (at UC Irvine), theatre theoretician (two of his works were partially translated to Romanian, Acting Power under the title Puterea interpretării scenice, Casa Cărții de Știință, 2007 and More Power to You, as Eseuri despre Teatru, Casa Cărții de Știință, 2012), playwright (his plays Machiavelli: The Art of Terror and Bzzap! were translated to Romanian, published and staged at the National Theatre in Cluj in 2009 and 2016, respectively), and theatre director (his stagings of Brian Reynold’s Railroad and Blue Shade were presented at Romanian theatre festivals in 2006 and 2007), Robert Cohen has prepared, in A Director’s Theatre, another surprise for Romanian theatre specialists.